THE ROLE OF LINGUISTICS IN DISCOURSE ANALYSIS - Davurova Umida Jo'raqul qizi (Western European Studies, 2025)
In this article, the role and importance of the speech analysis of linguistics in this article is covered. The structure, content and functional features of the speech are analyzed on the basis of linguistics approaches. In particular, the contribution of programs, pragmatics and stylistics to the analysis of the analysis of the speeches will be considered. In this article, the practical application of linguistics through the analysis of speech units, context and communicative intentions. The results of the study show the importance of speech analysis in areas such as language studies, translation, literature and the media
Keywords: Linguistics; speech analysis; Discussion